2022
DOI: 10.1186/s12882-022-02850-3
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of urate-lowering agents in asymptomatic hyperuricemia: systematic review and network meta-analysis of randomized controlled trials

Abstract: Background Asymptomatic hyperuricemia was found to be associated with increased cardiovascular disease risk but the potential benefits of urate-lowering therapy (ULT) remain controversial. We conducted a systematic review and network meta-analysis (NMA) with frequentist model to estimate the efficacy and safety of ULT in asymptomatic hyperuricemia. Methods MEDLINE, Embase, and Scopus were searched without language restrictions. Randomized controlle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 74 publications
1
8
0
Order By: Relevance
“…Respecting the evaluation of uric acid-lowering treatment and its relation to BP, allopurinol dose was not a factor independently associated with BP in the group of patients without anti-hypertensive drug intake in our study. This is consistent with multiple studies [ 18 21 ]. Some meta-analyses regarding this subject conclude the evidence is insufficient to unequivocally confirm the hypotensive effect of uric acid-lowering agents in hypertensive patients [ 25 ].…”
Section: Discussionsupporting
confidence: 94%
“…Respecting the evaluation of uric acid-lowering treatment and its relation to BP, allopurinol dose was not a factor independently associated with BP in the group of patients without anti-hypertensive drug intake in our study. This is consistent with multiple studies [ 18 21 ]. Some meta-analyses regarding this subject conclude the evidence is insufficient to unequivocally confirm the hypotensive effect of uric acid-lowering agents in hypertensive patients [ 25 ].…”
Section: Discussionsupporting
confidence: 94%
“…One might hope that meta-analyses might help resolve the issues, but even here there remains confusion, because some recent studies suggest that treatment of asymptomatic hyperuricemia in CKD does slow progression, 52 , 53 whereas others are mixed or indeterminant, 50 , 54 , 55 and some are negative. 56 Some meta-analyses show benefit with only specific urate-lowering drugs, such as febuxostat.…”
Section: Gout and Ckdmentioning
confidence: 99%
“…A recent network meta-analysis including 23 double-blind, placebo-controlled, randomized clinical trials carried out with different SUA lowering drugs concluded that allopurinol and febuxostat had significantly lower composite renal events (deterioration of renal function, end-stage renal disease, and initiation of renal replacement therapy) than placebo (Relative Risk - RR 0.39, 95% CI 0.23–0.66, and RR 0.68, 95% CI 0.46–0.99, respectively), but no apparent effect on major CV events [ 49 ]. A larger meta-analysis including 30 trials (N = 18,585) concluded that xanthine oxidase inhibitors produced a 6.0% reduction in relative risk for major adverse cardiovascular events, mainly because of the benefit attributed to allopurinol (RR: 0.61, 95% CI 0.46–0.80, I 2 = 21.0%), while febuxostat would have a more neutral effect (RR: 1.09, 95% CI 0.998–1.19, I 2 = 0.0%) [ 50 ].…”
Section: Discussionmentioning
confidence: 99%